2008
DOI: 10.1161/circulationaha.107.738740
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Alcohol Septal Ablation for Obstructive Hypertrophic Cardiomyopathy

Abstract: Background-The clinical efficacy of alcohol septal ablation for drug-refractory hypertrophic cardiomyopathy remains unclear. This study examines the outcome of alcohol septal ablation performed at a tertiary hypertrophic cardiomyopathy referral center. Methods and Results-Among 601 patients with severely symptomatic obstructive hypertrophic cardiomyopathy referred for alcohol septal ablation or myectomy from 1998 to 2006, 138 patients (median age, 64 years; 39% men) chose to undergo ablation. Procedural compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
184
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(207 citation statements)
references
References 46 publications
16
184
1
6
Order By: Relevance
“…However, we are still not sure whether this technique extends longevity of its target patients. Results from several studies suggest that ASA can extend longevity of patients with HCM [6][7][8][9][10][11][12]. Here, we extended evidence for this notion by directly comparing the survival of patients undergoing ASA vs. a group of conservatively treated patients with comparable pressure gradient and limiting symptoms.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, we are still not sure whether this technique extends longevity of its target patients. Results from several studies suggest that ASA can extend longevity of patients with HCM [6][7][8][9][10][11][12]. Here, we extended evidence for this notion by directly comparing the survival of patients undergoing ASA vs. a group of conservatively treated patients with comparable pressure gradient and limiting symptoms.…”
Section: Discussionmentioning
confidence: 64%
“…Studies have demonstrated that survival rates after ASA and myectomy in experienced centers were similar [6][7][8]. And, as survival after myectomy, survival after ASA is also comparable with that of general population [8,9].…”
Section: Introductionmentioning
confidence: 91%
“…In addition to diastolic dysfunction, septal scarring from ASA may contribute to rhythm abnormalities. An earlier Mayo Clinic study also showed a ventricular tachyarrhythmia and complications rate of 20% with ASA (31).…”
Section: Rv Myectomy For Hocm Patients With Septal Myocardial Fibrosismentioning
confidence: 82%
“…Sorajja et al 10 conclude that "in patients Ͻ65 years old, symptom relief is better after myectomy." I beg to differ.…”
Section: Article P 131mentioning
confidence: 99%